2008
DOI: 10.1111/j.1463-1326.2008.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia in patients with type 2 diabetes treated with a combination of metformin and sulphonylurea therapy in France

Abstract: The occurrence and severity of hypoglycaemic symptoms were associated with increased patient worry about hypoglycaemia and lower health-related quality of life among type 2 diabetic patients being treated with both metformin and a sulphonylurea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
61
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 29 publications
7
61
1
2
Order By: Relevance
“…45 An increase in the risk of hypoglycemia is well known with SU therapy and an increase in hypoglycemic events has been reported when these agents are used in combination with other antihyperglycemic drugs, such as metformin and GLP-1 agonists. 46,47 Adjustment of SU therapy to a lower dose should, therefore, be considered when adding linagliptin to pre-existing SU therapy. This is recommended in the prescribing information for linagliptin 9 and other DPP-4 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…45 An increase in the risk of hypoglycemia is well known with SU therapy and an increase in hypoglycemic events has been reported when these agents are used in combination with other antihyperglycemic drugs, such as metformin and GLP-1 agonists. 46,47 Adjustment of SU therapy to a lower dose should, therefore, be considered when adding linagliptin to pre-existing SU therapy. This is recommended in the prescribing information for linagliptin 9 and other DPP-4 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that between 24 and 60 % of patients with diabetes experience NSHEs [3][4][5][6], and symptoms can have a serious impact on a person's quality of life, health, psychological well-being, and adherence to treatment regimens [7]. Quality of life has further been shown to decrease as the frequency and severity of hypoglycemic events increase [4].…”
Section: Introductionmentioning
confidence: 97%
“…Sulfonylurea use is found to be associated with significantly higher incidence of hypoglycemia than with metformin [32]. Incidence and severity of hypoglycemia is reported to be associated with increased patient anxiety about hypoglycemia and lower health-related quality of life in T2DM patients under metformin and a SU treatment [33]. In comparison with SU, a SGLT2 inhibitor (dapagliflozin) is reported to cause significantly lower incidence of hypoglycemia (7% vs. 29%) [34].…”
Section: Discussionmentioning
confidence: 98%